Geographical inequalities in uptake of NHS funded eye examinations: Poisson modelling of small-area data for Essex, UK. (17th June 2017) - Shickle, Darren; Farragher, Tracey M; Davey, Chris J; Slade, Sarah V; Syrett, James
Abstract: Background: Small-area analysis of National Health Service (NHS)-funded sight test uptake in Leeds showed significant inequalities in access among people aged <16 or ≥60. Methods: Data were extracted from 604 126 valid General Ophthalmic Services (GOS)1 claim forms for eye examinations for Essex residents between October 2013 and July 2015. Expected GOS1 uptake for each lower super output area was based on England annual uptake. Poisson regression modelling explored associations in GOS1 uptake ratio with deprivation. Results: People aged ≥60 or <16 living in the least deprived quintile were 15% and 26%, respectively, more likely to have an NHS funded eye examination than the most deprived quintile, although all are equally entitled. GOS1 uptake is higher in the more deprived quintiles among 16–59-year old, as means tested social benefits are the main eligibility criteria in this age-group. Inequalities were also observed at local authority level. Conclusions: Inequalities in access among people ≥60 years were not as large as those reported in Leeds, although inequalities in <16-year old were similar. However, demonstrable inequalities in this data set over a longer time period and a larger and more diverse area than Leeds, reinforce the argument that interventions are needed to address eye examination uptake inequalities.